2010
DOI: 10.1578/am.36.4.2010.342
|View full text |Cite
|
Sign up to set email alerts
|

Trophic Transfer of the Harmful Algal Toxin Domoic Acid as a Cause of Death in a Minke Whale (<I>Balaenoptera acutorostrata</I>) Stranding in Southern California

Abstract: Unusually high concentrations of the neurotoxin domoic acid (DA) were detected in a minke whale (Balaenoptera acutorostrata) carcass recovered during a severe harmful algal bloom (HAB), which occurred in southern California in April 2007. Cell fragments of the toxigenic diatom Pseudonitzschia australis were observed in whale gastric fluid and feces, corresponding to a dominance of Pseudo-nitzschia spp. in the phytoplankton community at the time of stranding. A high abundance of otoliths from a prominent DA vec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 31 publications
2
42
0
Order By: Relevance
“…In April 2007, shellfish DA concentrations in SBB reached $600 ppm and were the highest recorded since the start of the monitoring program. This high concentration event coincided with the death of a minke whale attributed to DA-poisoning in SBB (Fire et al, 2010). Sediment trap collections began to detect particulate DA during the March 13-31, 2007 time period, with fluxes increasing from 3.9 to 177 mg m À2 d À1 by May 4, 2007 (Fig.…”
Section: Pseudo-nitzschia and Da Flux Time Series In Sbbmentioning
confidence: 81%
“…In April 2007, shellfish DA concentrations in SBB reached $600 ppm and were the highest recorded since the start of the monitoring program. This high concentration event coincided with the death of a minke whale attributed to DA-poisoning in SBB (Fire et al, 2010). Sediment trap collections began to detect particulate DA during the March 13-31, 2007 time period, with fluxes increasing from 3.9 to 177 mg m À2 d À1 by May 4, 2007 (Fig.…”
Section: Pseudo-nitzschia and Da Flux Time Series In Sbbmentioning
confidence: 81%
“…The production of DA by field populations of P. australis was first confirmed in Monterey Bay, California (USA) in 1991, during an ASP outbreak that caused massive deaths of pelicans (Pelecanus occidentalis) and cormorants (Phalacrocorax penicillatus) (Fritz et al, 1992;Garrison et al, 1992). Since then, numerous studies have confirmed DA production of this species in culture, as well as its association with poisoning episodes in marine birds and mammals (e.g., Míguez et al, 1996;Sierra-Beltrán et al, 1997;Fraga et al, 1998;Scholin et al, 2000;Cusack et al, 2002;Schnetzer et al, 2007;Fire et al, 2010;McCabe et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Southern California, USA frustules in gut and feces, DA in feces Fire et al (2010) Dwarf sperm whale Kogia sima U.S. southeast coast DA in urine and feces Fire et al (2009) Southern sea otter…”
Section: Balaenoptera Acutorostratamentioning
confidence: 99%